Characterization and repurposing of the endogenous Type I-F CRISPR–Cas system of Zymomonas mobilis for genome engineering. Issue 21 (24th October 2019) - Zheng, Yanli; Han, Jiamei; Wang, Baiyang; Hu, Xiaoyun; Li, Runxia; Shen, Wei; Ma, Xiangdong; Ma, Lixin; Yi, Li; Yang, Shihui; Peng, Wenfang
Abstract: Application of CRISPR-based technologies in non-model microorganisms is currently very limited. Here, we reported efficient genome engineering of an important industrial microorganism, Zymomonas mobilis, by repurposing the endogenous Type I-F CRISPR–Cas system upon its functional characterization. This toolkit included a series of genome engineering plasmids, each carrying an artificial self-targeting CRISPR and a donor DNA for the recovery of recombinants. Through this toolkit, various genome engineering purposes were efficiently achieved, including knockout of ZMO0038 (100% efficiency), cas2/3 (100%), and a genomic fragment of >10 kb (50%), replacement of cas2/3 with mCherry gene (100%), in situ nucleotide substitution (100%) and His-tagging of ZMO0038 (100%), and multiplex gene deletion (18.75%) upon optimal donor size determination. Additionally, the Type I-F system was further applied for CRISPRi upon Cas2/3 depletion, which has been demonstrated to successfully silence the chromosomally integrated mCherry gene with its fluorescence intensity reduced by up to 88%. Moreover, we demonstrated that genome engineering efficiency could be improved under a restriction–modification (R–M) deficient background, suggesting the perturbance of genome editing by other co-existing DNA targeting modules such as the R–M system. This study might shed light on exploiting and improving CRISPR–Cas systems in other microorganisms for genome editing and metabolic engineering practices.